Philosophers of the Renaissance - McNeil, Brian; Blum, Paul Richard (Book collections on Project MUSE., 2010)
"Philosophers of the Renaissance introduces readers to philosophical thinking from the end of the Middle Ages through the sixteenth century. International specialists portray the thought of twenty-one individual philosophers, illustrating their life and work and highlighting the importance of their thinking. The book weaves together their stories by emphasizing the unity of Renaissance philosophy in its attempt to find a philosophical method, combine religious and political thought, analyze language, and discuss the practical dimension of philosophy. Originally published in German in 1998, the chapters have been thoroughly revised and updated. A chapter on Luis Vives was written specifically for this English edition; an extensive bibliography introduces the reader to the current research on philosophers of the Renaissance"--Jacket.